Defining the fringe of contemporary Australian archaeology : pyramidiots, paranoia and the paranormal - Bosco, Rocco; Jordan, Darran (Cambridge Scholars Publishing, 2018)
Popular culture has often presented a mythologised version of archaeology that at times misinforms the general public about broader academic intentions. The fantastic and bizarre continue to capture the public imagination, so that while archaeological teams excavate, survey and record, they occupy the same geographic locations as ghost tour operators and seekers of the supernatural. Not only does archaeology operate within the same geography as modern mythology, but widespread access to technology, from satellite imagery to GPS data, means that enthusiastic amateurs can partake in their own in.